Mixed-Integer Linear Programming (MILP) Approach for the Synthesis of Efficient Power-to-Syngas Processes - Maggi, Andrea; Wenzel, Marcus; Sundmacher, Kai (Frontiers in Energy Research, 2020)
Within the context of energy transition scenarios towards renewable resources, superstructure optimization is implemented for the synthesis of sustainable and efficient Power-to-Syngas processes. A large number of reactors (i.e. reverse water-gas-shift, steam reforming, dry reforming, tri-reforming, methane partial oxidation reactor, water electrolyzer) and separators (e.g. PSA, TSA, cryogenics, membranes, gas-liquid scrubbing) \textcolor{blue}{are included within a single MILP framework, accounting for typical operating conditions of each process-unit, under the specified simplifying assumptions. Power is minimized in the context of sustainable feedstocks: water and biogas or carbon dioxide from direct air-capture. The objective function adds the thermal to the electrical contribution to the total power, the latter being weighted by a pseudo-price of null -- i.e. sustainable, in-house electricity production -- or unitary value -- i.e. electricity purchased, possibly generated from non-sustainable sources. simultaneous operations of multiple reactor-technologies is allowed to identify possible synergies. With biogas and null value of the pseudo-price, the results identify plant configurations mainly run via electricity, which constitutes up to $97%$ of the total power for co-operating partial oxidation of methane and water electrolysis. Alternatively, lower total demands are attained at the expenses of thermal duty when electricity is penalized: the endothermic reactors are operated. With carbon dioxide, the total power demand dramatically increases due to the large consumptions of direct-air capture and water electrolysis. The resulting topologies always favor membrane separation, adsorption and cryogenics over absorption technologies.